2006
DOI: 10.1051/0004-6361:200600013
|View full text |Cite
|
Sign up to set email alerts
|

Phase asynchrony of the north-south sunspot activity

Abstract: Aims. Northern and Southern sunspot activities demonstrate striking synchronous behavior during a solar cycle. But sometimes synchronization fails and the north-south asymmetry occurs. The problem is the origin of the north-south asymmetry and its quasi-regular oscillations. Methods. We employed Cross-Recurrence Plot analysis to extract synchronization between the Northern and Southern sunspot activities. Results. By using Cross-Recurrence Plot technique and extracting line of synchronization we found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 12 publications
6
68
0
Order By: Relevance
“…In contrast to our previous analysis (Zolotova & Ponyavin 2006 in which raw (unsmoothed) data were analysed, we used filtered (smoothed) data. Smoothing of the data allows an accurate detection of the LOS in the CRP.…”
Section: Data and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to our previous analysis (Zolotova & Ponyavin 2006 in which raw (unsmoothed) data were analysed, we used filtered (smoothed) data. Smoothing of the data allows an accurate detection of the LOS in the CRP.…”
Section: Data and Resultsmentioning
confidence: 99%
“…It is also important to point out that CRPs require time series of the same observable and similar amplitude variations in both x and y. However, a CRP can be useful for detecting differences in timescales between two different data series or dynamical systems, as shown for geophysical measurements of lake sediments (Marwan et al 2002;Marwan & Kurths 2005) or phase differences in the occurence of sunspots (Zolotova & Ponyavin 2006). CRPs were initially introduced to study dynamical systems of higher dimensions, i.e., by considering phase space vectors x ∈ R m , but can be analogously applied to the analysis of spatio-temporal data (Vasconcelos et al 2006;Marwan et al 2007a,b), as in the case of sunspot activity data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One may also wish to check its validity of some research on the latitudinal migration of solar activity. For example, some researchers have reported that latitudinal migration of sunspots asynchronously occur in the northern and southern hemispheres (Waldmeier 1971, Swinson et al 1986, Zolotova & Ponyavin 2006, Donner & Thiel 2007, Zolotova et al 2009, Li et al 2009a, b, 2010. They have attempted to explain the solar North-South asymmetry with such a phase difference between paired wings of the butterfly diagram instead of appreciating the real asymmetry in two hemispheres.…”
Section: Center-of-latitude Of Sunspotmentioning
confidence: 99%